2021
DOI: 10.1038/s41467-021-24332-0
|View full text |Cite
|
Sign up to set email alerts
|

A release-and-capture mechanism generates an essential non-centrosomal microtubule array during tube budding

Abstract: Non-centrosomal microtubule arrays serve crucial functions in cells, yet the mechanisms of their generation are poorly understood. During budding of the epithelial tubes of the salivary glands in the Drosophila embryo, we previously demonstrated that the activity of pulsatile apical-medial actomyosin depends on a longitudinal non-centrosomal microtubule array. Here we uncover that the exit from the last embryonic division cycle of the epidermal cells of the salivary gland placode leads to one centrosome in the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 74 publications
(122 reference statements)
2
20
1
Order By: Relevance
“…The microtubule reorganization we observe differs from recent studies that have demonstrated an interplay between the two cytoskeletal systems in two ways: first, microtubule reorganization occurs in the apical plane rather than along the apicobasal axis; second, the consequences, of the perturbations tested, on actomyosin and microtubule cytoskeleton are also different (Booth et al, 2014;Ko et al, 2019;Gillard et al, 2021).…”
Section: The Importance Of Apical Microtubule Network Reorganization ...contrasting
confidence: 97%
“…The microtubule reorganization we observe differs from recent studies that have demonstrated an interplay between the two cytoskeletal systems in two ways: first, microtubule reorganization occurs in the apical plane rather than along the apicobasal axis; second, the consequences, of the perturbations tested, on actomyosin and microtubule cytoskeleton are also different (Booth et al, 2014;Ko et al, 2019;Gillard et al, 2021).…”
Section: The Importance Of Apical Microtubule Network Reorganization ...contrasting
confidence: 97%
“…The levels of apical-medial Patronin were still sufficient to capture microtubule-minus ends released by Katanin, thereby generating the non-centrosomal microtubules that will then form the longitudinal array as we showed previously (Gillard et al, 2021). These data illustrate that not only the longitudinal microtubule array but also apicalmedial b-H-Spectrin are both required to support apical-medial actomyosin assembly and function to drive apical constriction.…”
Section: B-h-spectrin Is Required For Apical Constriction and The Ass...supporting
confidence: 74%
“…The disappearance of apical MTs is not driven by a shift of the centrosome position 33 (Supplementary Fig. 3k ), nor relocalisation of MTs or a change of MTs association with the centrosome 35 , or modulation of the localisation of the non-centrosomal MTs organisers Patronin and Shot 33 , 36 , 37 (Supplementary Fig. 3i, j ).…”
Section: Discussionmentioning
confidence: 97%